2011
DOI: 10.1007/s00535-011-0506-7
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous orexin-A in the brain mediates 2-deoxy-d-glucose-induced stimulation of gastric motility in freely moving conscious rats

Abstract: Running head; Orexin and gastric motility 2 Abstract Background. Increasing evidence has indicated that brain orexin plays a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 46 publications
(46 reference statements)
1
9
0
Order By: Relevance
“…In contrast, 2-DG-stimulated acid production was inhibited by nesfatin-1 in a dose-dependent manner. As 2-DG is known to trigger gastric acid secretion by activation of the vagal center (10,19,32), our study indicates that nesfatin-1 suppresses vagally stimulated gastric acid production.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In contrast, 2-DG-stimulated acid production was inhibited by nesfatin-1 in a dose-dependent manner. As 2-DG is known to trigger gastric acid secretion by activation of the vagal center (10,19,32), our study indicates that nesfatin-1 suppresses vagally stimulated gastric acid production.…”
Section: Discussionsupporting
confidence: 52%
“…Systemic administration of 2-DG initiates a state of simulated cytoglycopenia, leading to altered hypothalamic input to the dorsal-vagal complex (DVC) in the brain stem and resultant activation of bilateral vagus nerves (10,19,30). 2-DG has been widely used to study gastric acid secretion mediated by the vagus nerve (19,32,36). Using gastrin and 2-DG to evaluate peripheral and central mechanisms of stimulated acid production, we have explored the effects of centrally administered nesfatin-1 on gastric acid secretion.…”
mentioning
confidence: 99%
“…Consistent with our finding, previous studies have revealed that endogenous orexin systems play important roles in the regulation of gastrointestinal function, motor learning and visceral sensation. For example intracisternal injection of SB-334687 suppressed gastric contractions induced by central vagal stimulation or acute restraint stress (B€ ulb€ ul et al, 2010;Nozu et al, 2012). Furthermore, endogenous orexins modulated the activity of Purkinje cells in the cerebellum and therefore participated in motor learning (Chen et al, 2013).…”
Section: Endogenous Orexin-a Modulates the Spontaneous Firing Activitmentioning
confidence: 99%
“…The method used in the present study had already established well to measure GI contractions [13,[15][16][17][18]. Non-fasted rats were placed in a wire-bottom and non-restraint polycarbonate cage.…”
Section: Manometric Recordings and Study Designmentioning
confidence: 99%